There Is No Relationship Between The Level Of Zinc Consumption And The Incidence Of Anemia In Female Workers At The Badung Mall, Bali - Ida Ayu Eka Padmiari; Ni Nengah Ariati; G A Dewi Kusumayanti; Pande Putu Sri Sugiani (International Journal of Health Engineering and Technology, 2023)
Women workers are included in the group of women of childbearing age  who are prone to health problems due to the low intake of nutrients consumed. The low intake of nutrients consumed and the bleeding experienced during menstruation can affect hemoglobin levels and productivity in workers. The health problem that is often experienced by female workers is anemia. Anemia is a condition where the level of hemoglobin in the blood is below the normal value. This study aims to determine the relationship between the level of consumption of micronutrients (iron, zinc, folic acid, and vitamin C) with the incidence of anemia in female workers at Mall Badung. The research design used was cross-sectional with a sample of 35 female workers at Mall. The data taken were Hb levels using the easy touch tool, and food intake data obtained using a 24-hour recall form. Data analysis used the Pearson Product Moment Correlation and Spearman Rank Correlation tests. The results showed that the proportion of anemia was 22,9%. The average Hb level obtained was 13,8 g/dL. The average level of consumption of iron (86,2%), zinc (80,6%), folic acid (84,9%), and vitamin C (93,7%). Based on the results of the correlation test showed that there was a significant relationship between the level of iron consumption (p-value = 0,000), folic acid (p-value = 0,009), and vitamin C (p-value = 0,026) with the incidence of anemia in female workers and there was no relationship between levels of consumption of zinc (p-value = 0,601) with the incidence of anemia in female workers..